Different temperature responses of mountain rockwalls, soils, and lakes to summer heat waves - Rosalie Bruel; Florent Arthaud; Florence Magnin; Raphaëlle Napoleoni; Colin Van Reeth; Vincent Augé; Clotilde Sagot; Mathieu Fructus; Carole Birck; Philippe Choler (Regional Environmental Change, 2026)
Mountain ecosystems are highly sensitive to climate variations. At fine spatial scales, high-elevation microclimates play a critical role in shaping biodiversity, hydrological processes, and ecosystem services, while also influencing the occurrence of natural hazards such as landslides, avalanches, and floods. Heat waves, which have been increasing in frequency and intensity due to global climate change, present significant challenges to these vulnerable environments. This study examines the impacts of summer heat waves on mountain microthermal conditions in three compartments: rockwalls, soils, and lakes. We assembled data across a latitudinal and elevational gradient in the French Alps including years of two recent heat wave events (2015 and 2022). We calculated thermal indicators to evaluate the buffering or amplifying effects of the atmospheric signal on the investigated compartments. The average summer temperature and the growing/thawing degree days were more responsive to heat waves than the phenological indicator (e.g., spring mixing date in lakes) and maximum temperature. We found significant anomalies for both the 2015 and 2022 heat waves across almost all compartments and indicators. Lakes tended to amplify atmospheric temperatures (especially in 2022) whereas rockwalls and soils tended to buffer them. However, residues from the relationship between compartment and atmospheric temperatures were large during heat waves, suggesting that these events may reduce the compartments’ buffering capacity. Our study underscores the importance of long-term monitoring of microthermal conditions to provide a more integrative assessment of mountain ecosystem response to extreme meteorological events. Graphical abstract